Conversion Surgery Following Immunochemotherapy in Initially Unresectable Locally Advanced Esophageal Squamous Cell Carcinoma—A Real-World Multicenter Study (RICE-Retro) - Huang, Shujie; Wu, Hansheng; Cheng, Chao; Zhou, Ming; Xu, Enwu; Lin, Wanli; Wang, Guangsuo; Tang, Jiming; Ben, Xiaosong; Zhang, Dongkun; Xie, Liang; Zhou, Haiyu; et al. (Frontiers in Immunology, 2022)
Purpose: The present study set out to evaluate the feasibility, safety and effectiveness of conversion surgery following induction immunochemotherapy for patients with initially-unresectable locally advanced esophageal squamous cell carcinoma (ESCC) in a real-world scenario. Materials and Methods: In this multi-center, real-world study (NCT04822103), patients who had unresectable ESCC disease were enrolled across eight medical centers in China. All patients received programmed death receptor-1 (PD-1) inhibitor plus chemotherapy every three weeks for at least two cycles. Patients with significant relief of cancer-related clinical symptoms and radiological responsive disease were deemed surgical candidates. Feasibility and safety profile of immunochemotherapy plus conversion surgery, radiological and pathological tumor responses as well as survival outcomes were evaluated. Moreover, data of an independent ESCC cohort receiving induction chemotherapy (iC) were compared. Results: One hundred and fifty-five patients were enrolled in the final analysis. Esophagectomy was offered to 116 patients, yielding a conversion rate of 74.8%. R0 resection rate was 94%. Significant differences in responsive disease rate was observed between iC cohort and iIC cohort (ORR: iIC 63.2% vs. IC 47.7%, p = 0.004; pCR: iIC 22.4% vs. iC 6.7%, p = 0.001). Higher anastomosis fistula rate was observed in iC group (19.3%) compared to iIC group (4%). Furthermore, Significantly higher event-free survival was observed in those who underwent conversion surgery. Conclusion: Our results supported that conversion surgery following immunochemotherapy is feasible and safe for initially-unresectable locally advanced ESCC patients. Both radiological and pathological response rates were significantly higher in the iIC cohort compared to those in the traditional iC cohort.